A Shorter-Bout of HIIT Is More Effective to Promote Serum BDNF and VEGF-A Levels and Improve Cognitive Function in Healthy Young Men - Li, Qing; Zhang, Li; Zhang, Zhengguo; Wang, Yuhan; Zuo, Chongwen; Bo, Shumin (Frontiers in Physiology, 2022)
Objective: The aim of this study was to investigate the effects of single bouts of high-intensity interval training (HIIT) with different duration on serum brain-derived neurotrophic factor (BDNF) and vascular endothelial growth factor-A (VEGF-A) levels and cognitive function in healthy young men. Methods: Twelve healthy young men were participated in two HIIT treatments (20minutes HIIT and 30minutes HIIT) in a random order. BDNF, VEGF-A, cortisol, testosterone, blood lactic acid were measured and cognitive function was assessed by Stroop test (CWST) and Digital Span test (DST) before, immediately after, and 30 minutes after HIIT. Results: 20 minutes and 30 minutes HIIT increased BLa (both P<0.01), cortisol (20 minutes HIIT: P<0.05; 30 minutes HIIT: P<0.01), and testosterone (both P<0.05) levels immediately when compared with their baselines. While BLa and cortisol were significantly higher in 30 minutes HIIT group than in 20 minutes HIIT group. Moreover, BDNF concentration (P<0.01), DST-F (P<0.01) and DST-B (P<0.05) were increased and response time of Stroop was decreased immediately after HIIT only in 20 minutes HIIT group. VEGF-A concentration was increased immediately after HIIT in both groups (P<0.01), but after 30 minutes recovery, it was returned to the baseline in the 20 minutes HIIT group and was lower than the baseline in 30 minutes HIIT group (P<0.05). Conclusion: Twenty minutes HIIT is more effective than thirty minutes HIIT for promoting serum levels of BDNF and VEGF-A as well as cognitive function in healthy young men.